EFFORTS OF CORRECTIONAL INSTITUTIONS IN FOSTERING RECIDIVIST INMATES - Andri Yani, Reni; Diah Gustiniati; Fristia Berdian Tamza (Faculty of Law-Universitas Bandar Lampung, 2025)
Correctional Institutions (Prisons) play an important role in the rehabilitation of inmates with the aim of preparing them to be able to reintegrate into society productively and responsibly. Coaching programs in prisons, which include mental, spiritual, skillful, and educational aspects, are designed to reduce recidivism by helping inmates understand social and legal norms. However, the high rate of recidivism in Indonesia shows that the program is not yet fully effective. Factors such as social stigma, difficulty in getting a job, limited facilities, lack of family support, and the lack of deterrent effects of criminal punishment also make it difficult for former inmates to live a better life post-release. Therefore, a more holistic approach to the penitentiary system is needed, which focuses not only on corporal punishment but also on thorough rehabilitation involving skills training, education, and psychological support to increase the chances of ex-convicts living a crime-free life.